Educational Administration Students’ Satisfaction With SYAM-OK Academic Information Service at Universitas Negeri Makassar - By Tri Agung Nusantara Kr. J. Tompong; Andi Ratu Ayuashari Anwar (Jurusan Teknik Informatika dan Komputer, 2025)
This study aims to analyze the level of satisfaction among students, as the primary users, with the quality of the academic information system SYAM-OK at Universitas Negeri Makassar (UNM). The academic information system is a vital component in supporting academic administration and learning processes, especially in the digital era that demands fast and accurate information access. This research employed a qualitative descriptive method with data collected through in-depth interviews with students actively using SYAM-OK. Respondents were students from the Educational Administration Department, Faculty of Education, UNM. The findings indicate that students are generally satisfied with SYAM-OK as it facilitates access to academic information, such as class schedules, transcripts, and important announcements. However, some technical issues remain, such as difficulties submitting assignments due to internet disruptions and server overload. The study recommends improving technological infrastructure, intensive training for lecturers to optimize interactive features, and the development of additional features, such as email notifications and offline access. Implementing these recommendations is expected to enhance the quality of SYAM-OK services, making them more effective in supporting academic activities.